2021
DOI: 10.1186/s12891-021-04155-2
|View full text |Cite
|
Sign up to set email alerts
|

Early surgery with antibiotic medication was effective and efficient in treating pyogenic spondylodiscitis

Abstract: Background Pyogenic spondylodiscitis (PSD) is challenging to the orthopedist with regards to diagnosis and treatment. The present study was designed to assess and suggest the most indicative diagnostic method and evaluate the effect of surgery comprising of debridement, instrumentation and fusion in treating PSD. Methods Seventy-six patients with PSD who underwent surgical intervention were retrospectively enrolled. Their medical documents, correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…One recent study found that the identification of the pathogen could only have been conducted in 22.4% of the patients with pyogenic spondylodiscitis [47]. Postoperative antibiotic therapy was managed against the result of the susceptibility test, or was empirically given to patients with negative cultures with all antibiotic therapy IV initiated for 4-6 weeks and orally for 6 weeks [47].…”
Section: Value Of Measurement Of Laboratory Infection Parametersmentioning
confidence: 99%
“…One recent study found that the identification of the pathogen could only have been conducted in 22.4% of the patients with pyogenic spondylodiscitis [47]. Postoperative antibiotic therapy was managed against the result of the susceptibility test, or was empirically given to patients with negative cultures with all antibiotic therapy IV initiated for 4-6 weeks and orally for 6 weeks [47].…”
Section: Value Of Measurement Of Laboratory Infection Parametersmentioning
confidence: 99%
“…At the moment of writing, no guidelines for the conservative and surgical treatments of PSD are yet available. Thus, the current pediatric practice is derived from the management of adult spondylodiscitis (12)(13)(14) and relies upon the experience of the treating clinicians. After clinical suspicion of PSD is risen, contrast-enhanced magnetic resonance imaging is the investigation of choice for the description of the infected site location and extension (3).…”
Section: Considerations On Psd Managementmentioning
confidence: 99%
“…The average operating time is 162.9-375 minutes, average blood loss is 1152-1470 mL, the average corrected lordotic angle is 6.1 ± 10.3°, and the average stay in the spine unit is 30 days [ 33 ]. Many patients experience immediate relief of pain and reduction of fever, and the anterior approach minimizes the damage done to the paraspinal muscles and bones [ 34 ]. However, 10% have infection recurrence, 6.3% require revision surgery, and 14.6% of patients die [ 33 ].…”
Section: Surgical Managementmentioning
confidence: 99%
“…This procedure is most often used when the thoracic spine is involved and/or an epidural abscess is present [ 38 ]. The spinal process and laminae are removed, followed by the removal of the diseased vertebrae [ 34 ]. A PEEK bone graft cage is then placed.…”
Section: Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation